The Effect of Drawing Art Therapy on the Anxiety Level of Students at Nurul Falah Vocational High School in Online Learning Assignments during the Covid-19 Pandemic in Geger Village, Mangaran District, Situbondo - Nur Yeny Hidajaturrokhmah; Yofan Nurmansyah; Amarin Yudhana (Journal of Global Research in Public Health, 2022)
With the Covid-19 pandemic, as an effort to prevent the spread, so there will be changes to learning methods in 2020 to 2021, due to a change in online or online learning, so there will be anxiety among students at Nurul Falah Mangaran Middle School. The purpose of this study was to determine the effect of drawing art therapy on reducing student anxiety at Nurul Falah Vocational School in online learning assignments during the co-19 pandemic in Geger village, Mangaran subdistrict.This research is a pre-experimental study using a quasi-experimental research design model of one group design with pre-test and post-test. The study population consisted of 42 respondents and the number of samples was 39 respondents using random sampling technique. The instrument uses the HARS questionnaire. statistical test using the Paired t test with SPSS software version 24 windows. Based on the results of the study, the anxiety of 39 respondents before drawing therapy had an anxiety value of 40.97 and after drawing therapy had an anxiety value of 10.41. based on statistical test results using Windows SPSS 24 Paired - Samples T Test obtained p = 0.000 with a significant level of α = 0.05 (ρ = 0.000 < α = 0.05). This means that there is an effect of drawing therapy on reducing anxiety in class XI students of Nurul Falah Vocational School with an anxiety score of 10.41. From this study, art therapy was very effective in overcoming psychological problems such as anxiety experienced by students during a pandemic.